(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fuel cell based electrical energy is sustainable, environment friendly, and economical. Among different fuel cell categories like proton exchange membrane (PEM), alkaline, direct methanol, phosphoric acid, molten carbonate, solid, and microbial fuel cells, PEM fuel cell is the most suitable for rural areas as it does not require any material other than water for generating electrical power. Using the same cell in electrolysis mode, the input water can be dissociated into hydrogen and oxygen using solar energy. The gases liberated may be stored for generating electrical power whenever there is a need. But the main problem of using water in rural areas for generating hydrogen and oxygen is the electrode corrosion as the water found in these areas is not pure. The impurities accumulated inside the system degrade the performance of the cell. A novel technique based on ion exchange stack layer made up of Tin(IV) arsenatungstate has been proposed and investigated in this paper for reducing the effect of corrosion on the electrodes. The analysis of the results based on pH measurements, visual inspection of the electrodes, and XRD studies shows that the proposed technique is capable of reducing the effect of impurities on the fuel cell electrodes.